Em busca de uma educação em direitos humanos e da natureza, como base para um desenvolvimento sustentável - Melo, Natália de Oliveira (2019)
The study presented here articulates two concepts, which occupy a central place in the contemporary world – Human Rights and Sustainable Development. The questioning is based on the indigenous concept of “living well” which understands that when discussing the future of the planet, this discussion cannot be reduced to the relation between human beings and the environment. At the centre of the discussion is a broad understanding of the concept of the right to life, which covers all forms of life – human, animal and vegetable. We defend that the right to a dignified life includes everything that has life. In this sense, and in consonance with ‘living well’, we argue for an education in and for human and natural rights as a basis for sustainable development. To that end, we analyse three recent documents concerning human rights: the National Plan of Human Rights, in its third version, dated 2010 (PNDH-3), the National Plan of Education in Human Rights, launched in 2007 (PNEDH), and the National Guidelines for Education in Human Rights, of 2012. The 2030 Agenda for Sustainable Development and the 2030 Agenda for Education were also the objective of analysis. The study of the concept of ‘living well’ and the concept of development, which it contains, was based on Latin American authors and was related with the concept of development, which underlies the Sustainable Development Goals. The research is essentially qualitative, bibliographic and documental, based on an understanding of documents as artefacts produced by humans in a determined conjuncture in order to communicate something. At the same time, it can be classified as an exploratory study whose objective is to clarify and to criticise concepts. For the data analysis, we utilised the technique of hermeneutic dialectics. We conclude that the concept of development, which emerges from the analysis of ‘living well’, possesses a holistic and harmonious vision of the elements, which guarantees a process of development for the entire planetary collective. On the contrary, in the 2030 Agenda an individualistic sentiment is present in a clearly anthropocentric perspective. Consequently, education in and for human rights is insufficient in order to guarantee the future of planetary life: for this, we defend an education in and for human and natural rights.